On the Relationship Between Tropical Instability Waves and Intraseasonal Equatorial Kelvin Waves in the Pacific From Satellite Observations (1993–2018) - Escobar-Franco, M. Gabriela; Boucharel, Julien; Dewitte, Boris (Frontiers in Marine Science, 2022)
Intraseasonal Kelvin waves (IKWs) and Tropical Instability Waves (TIWs) are essential components of the tropical Pacific coupled climate variability. While downwelling IKWs are precursors of ENSO (e.g., the El Niño Southern Oscillation), TIWs contribute to its asymmetry by mixing more/less warm off-equatorial and cold tongue waters during La Niña/El Niño. Theoretical studies and a few observational case studies also suggest that TIWs and IKWs can interact non-linearly. However, owing to the chaotic nature of TIWs, observational evidence that such a process occurs consistently has not been established thus far. Here, we document for the first time their interaction from satellite observations over a period spanning almost 30 years (1993–2018). From complex empirical orthogonal functions analysis and sea level decomposition into meridional modes, we evidence that a substantial share (∼42%) of the variance of TIWs-induced intraseasonal sea level anomalies are associated with IKWs activity. We show that non-linear dynamical heating (NDH) in the Eastern equatorial Pacific associated with this intraseasonal mode can be as large as that for interannual time scales. Implications for understanding the eastern tropical Pacific heat budget and ENSO variability are discussed.